2009
DOI: 10.1097/inf.0b013e3181ab603c
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Influenza Test in Young Febrile Infants for the Identification of Low-Risk Patients

Abstract: We included 381 febrile infants less than 3 months with a blood culture and a rapid influenza test done as part of study of fever. The prevalence of serious bacterial infections was significantly lower in patients in the positive rapid influenza test (RIT) group (3/113; 2.65%; 95% CI: 0-5.6) than in patients in the negative RIT group (47/268; 17.5%; 95% CI: 13-22.0). No patient with a positive RIT had a positive blood culture (vs. 8 in the negative RIT group, 2.98%, 95% CI: 0.9-5.0) The cerebrospinal fluid cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 11 publications
2
15
1
2
Order By: Relevance
“…Our findings support previous studies, which found low rates of concurrent SBI in young children with influenza . These studies used POCT to diagnose influenza and documented a rate of SBI of 1.8% in influenza‐positive children aged 0–36 months and rates of 2.5–2.65% for children <3 months of age .…”
Section: Discussionsupporting
confidence: 91%
“…Our findings support previous studies, which found low rates of concurrent SBI in young children with influenza . These studies used POCT to diagnose influenza and documented a rate of SBI of 1.8% in influenza‐positive children aged 0–36 months and rates of 2.5–2.65% for children <3 months of age .…”
Section: Discussionsupporting
confidence: 91%
“…Based on the fairly mild course of influenza A in infants and studies showing significantly reduced serious bacterial infections in infants ≥28 days, it has been argued that the management of young infants with influenza infections should be changed in terms of performing less extensive laboratory and radiological studies 5. While our study is supportive of the fact that influenza infections are relatively mild in young infants, over 10% of the infants in our study had a coexisting serious bacterial infection.…”
Section: Discussionsupporting
confidence: 62%
“…In multivariable analysis a positive viral identification reduced the likelihood of SBI in young infants with febrile illness. A number of prospective studies corroborated this finding in young infants with respiratory syncytial virus48 and influenza,49 50 though the presence of virus alone was insufficient to rule out SBI. The impact of respiratory viral testing was summarised in a Cochrane review of randomised controlled trials including more than 1500 children.…”
Section: Discussionmentioning
confidence: 84%